Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1021/ja051272a
|View full text |Cite
|
Sign up to set email alerts
|

CdO as the Archetypical Transparent Conducting Oxide. Systematics of Dopant Ionic Radius and Electronic Structure Effects on Charge Transport and Band Structure

Abstract: A series of yttrium-doped CdO (CYO) thin films have been grown on both amorphous glass and single-crystal MgO(100) substrates at 410 degrees C by metal-organic chemical vapor deposition (MOCVD), and their phase structure, microstructure, electrical, and optical properties have been investigated. XRD data reveal that all as-deposited CYO thin films are phase-pure and polycrystalline, with features assignable to a cubic CdO-type crystal structure. Epitaxial films grown on single-crystal MgO(100) exhibit biaxial,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(105 citation statements)
references
References 35 publications
6
99
0
Order By: Relevance
“…This is surprising since In 3+ has a smaller ionic radius (In 3+ 0.94 Å compared to Cd 2+ 1.09 Å) and the lattice parameter is expected to shrink with increasing In concentration. Lattice shrinkage and a decrease in grain size of ICO films prepared by other techniques have been observed [14,30]. According to Table 1, it is known that the film crystalline quality does not deteriorate significantly with increasing In concentration.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This is surprising since In 3+ has a smaller ionic radius (In 3+ 0.94 Å compared to Cd 2+ 1.09 Å) and the lattice parameter is expected to shrink with increasing In concentration. Lattice shrinkage and a decrease in grain size of ICO films prepared by other techniques have been observed [14,30]. According to Table 1, it is known that the film crystalline quality does not deteriorate significantly with increasing In concentration.…”
Section: Discussionmentioning
confidence: 83%
“…Table 2 shows the electrical properties of the pulsed arc-grown ICO films compared to values reported for several other growth techniques. Except for the optimized PLD-grown films [19], the electrical properties of films prepared by PFCAD in this study are typically better than those of ICO films prepared by other techniques on glass or even on single crystalline MgO substrates [10,12,14,30,[33][34][35][36]. Though the as-deposited films in this study show a little higher resistivity than that of the optimized PLD-grown films, comparable mobility with a higher near infrared transmittance and a much wider transparent range are observed, which is of special interest to multi-junction solar cells.…”
Section: Discussionmentioning
confidence: 84%
“…α(hv)=B〖(hv-E_g)〗^r (5) Where (B) is constant involving the properties of the bands,(υ) frequency of incident photon ,(r) is a constant depending on the nature of transition. From figure (7) It can be observed that the energy gap increased with increasing of Cu constrationfrom(2-3)eV.…”
Section: 3optical Propertiesmentioning
confidence: 99%
“…[5][6] Cadmium oxide has a high conductivity resulting from the presence of cadmium atoms in interstitial sites or due to oxygen vacuums [3]. Cadmium oxide has a high absorption factor that can be used in solar systems to increase its efficiency in photovoltaic cells and is used as window layers in Hetrojunction Solar Cells and transparent electrodes in solar cell technology.…”
Section: Introductionmentioning
confidence: 99%
“…12 NB semiconductors are colored or black when closed to stoichiometry, which is the case of β-PbO 2 , but may potentially become transparent when donor doped to high carrier concentrations, as it has been found for CdO, 13,14 thanks to the blue-shift of the optical band gap, following the Moss-Burstein effect. 15,16 The shift arises because the Fermi energy lies in the conduction band for heavy n-type doping and, consequently, the filled states block optical excitation.…”
mentioning
confidence: 98%